Development of an optical sensor based on surface plasmon resonance phenomenon for diagnosis of dengue virus E-protein - Sheh Omar, Nur Alia; Yap, Wing Fen; Abdullah, Jaafar; Che Engku Chik, Che Engku Noramalina; Mahdi, Mohd Adzir (Elsevier, 2018)
Application of surface plasmon resonance (SPR) optical sensor in the diagnosis of dengue virus (DENV) emerged over recent years. Immobilized monoclonal antibody (IgM) on gold/Fe-MPA-NCC-CTAB/EDC-NHS thin film was prepared using a spin coating technique. DENV E-protein can be detected by measuring the SPR signal when IgM immobilized gold/Fe-MPA-NCC-CTAB/EDC-NHS thin film is exposed to the DENV E-protein solution, by varying the concentration ranging from 0.0001 nM to 10 nM. A linear relationship between the shift of SPR angle and concentration of DENV E-protein up to 0.01 nM, with sensitivity of 39.96° nM−1 has been observed. The surface morphology of sensor chip was also recorded using atomic force microscopy to confirm the presence of bound DENV E-protein into IgM surface.